FRENCH CODE-MIXING IN ARABIZI ON SOCIAL MEDIA PLATFORM - Arif Rakhman; Yoyo Yoyo (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research paper explores the phenomenon of French code mixing in Arabizi within the Facebook group 'OFPPT: BTP & GÉNIE CIVIL.' The group comprises Arabic-speaking technicians and engineers from Morocco. The study aims to provide a comprehensive description of the French code mixing observed in this specific online community and investigates the factors influencing its occurrence. The sociolinguistic approach employed in this research incorporates the study of code mixing and its underlying causes. The primary data for analysis consisted of Arabic words, phrases, and technician-specific terminology found in uploads from January 2020 to December 2021 within the Facebook group 'OFPPT: BTP & GÉNIE CIVIL.' The data collection process involved note-taking techniques as well as screen captures and data tables for further analysis. The analysis of the collected data was conducted using referential and translational equivalent methods. The findings of this study reveal the presence of significant code mixing in Arabizi, combining elements of French and Arabic within the 'OFPPT: BTP & GÉNIE CIVIL' Facebook group. In its sociolinguistic context, French code mixing serves as an outer code mixing, while Arabic code-mixing functions as an inner code mixing. The Arab youth utilize this Arabizi code mixing to enhance their social standing, as French is perceived as a prestigious and modern language by them.